L-citrulline as Alternative Pharmacological Substance in Protecting Against Cardiovascular Disease - Laurentius, Andrea; Wikanendra, Gregorius Bhaskara; Cong, Tzeto Han; Arozal, Wawaimuli (Pharmaceutical Sciences and Research, 2018)
Cardiovascular disease (CVD) has taken up to average 30% of death diagnoses in the world. Prevalent attempts of physicians to treat this disease came down to focus on using drugs with their specific mechanism of action. Since the method only cures the symptoms and need to be pharmacologically monitored, physicians and scientists have been struggling to find other treatment strategies. This problem led us to search for another substance dealing with CVD via preventive therapy, which does not require such close monitoring by physicians in its use. The answer relies on using L-citrulline as potential therapeutics in treating and preventing CVDs. This compound, found mostly in Citrus sp., contains chemical traits that could affect other bodily substances with its metabolic pathways. It has several functions, but boosting NO production is the dominant one in the cardiovascular system. By enhancing NO bioavailability, it suppresses the risk of having myocardial oxidative stress due to ischemia, cardiac pressure-overload, and post-infarct reperfusion. Thus, understanding of L-citrulline effects on endothelial NOS pathway in the generation of NO and its uncoupling mechanisms could be used as a foundation in developing alternative treatment and prevention of oxidative stress-induced CVD.